The Link between Fetal Programming, Inflammation, Muscular Strength, and Blood Pressure - Jose Lopez-Lopez; Patricio Lopez-Jaramillo; Paul A. Camacho; Diego Gomez-Arbelaez; Daniel D. Cohen (Hindawi Limited, 2015)
Hypertension affects one billion individuals worldwide and is considered the leading cause of cardiovascular death, stroke, and myocardial infarction. This increase in the burden of hypertension and cardiovascular diseases (CVD) is principally driven by lifestyle changes such as increased hypercaloric diets and reduced physical activity producing an increase of obesity, insulin resistance, and low-grade inflammation. Visceral adipocytes are the principal source of proinflammatory cytokines and systemic inflammation participates in several steps in the development of CVD. However, maternal and infant malnutrition also persists as a major public health issue in low- to middle-income regions such as Latin America (LA). We propose that the increased rates of cardiovascular and metabolic diseases in these countries could be the result of the discrepancy between a restricted nutritional environment during fetal development and early life, and a nutritionally abundant environment during adulthood. Maternal undernutrition, which may manifest in lower birth weight offspring, appears to accentuate the relative risk of chronic disease at lower levels of adiposity. Therefore, LA populations may be more vulnerable to the pathogenic consequences of obesity than individuals with similar lifestyles in high-income countries, which may be mediated by higher levels of proinflammatory markers and lower levels of muscle mass and strength observed in low birth weight individuals.